Examining the antecedents of consumer conspicuous online buying behaviours for fine jewellery goods in Malaysia - Lau, Chuan Yee (2017)
Purpose- Like any business, its overall purpose is to generate wealth and determine sustainable and strategical growth, however it has become especially difficult for jewellery businesses to successful adopt technological changes as jewellers are trained to provide service in luxury retail store fronts. This study report adds to the exploratory knowledge of the technology acceptance in online commerce platforms in Malaysia. Aiming to provide an understanding to the trends of conspicuous buying behaviour by Malaysian on fine jewellery using online platforms and who they are; further calling for recommendations on whether Malaysian jewellery business owners should adopt to new technologies or fear losing to competition.